2002
DOI: 10.1103/physreve.66.016105
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition to frequency entrainment in a long chain of pulse-coupled oscillators

Abstract: A long chain of pulse-coupled oscillators was studied. The oscillators interacted via a phase response curve similar to those obtained from pacemaker cells in the heart. The natural frequencies were random numbers from a distribution with finite bandwidth. Stable frequency-entrained states were shown always to exist above a critical coupling strength. Below the critical coupling, the probability to have such states was shown to be zero if the number of oscillators is infinite. This discontinuity establishes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The next wave of work relaxed the all-to-all assumption by allowing oscillators to be connected to their nearest neighbors on a one-dimensional chain or ring, a two-dimensional square grid, or a higherdimensional cubic lattice [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . More recently, many researchers have explored the Kuramoto model on more complex topologies, allowing for nonlocal coupling 22 and small-world, scale-free, or other network architectures 6,7 .…”
Section: Introduction a The Kuramoto Modelmentioning
confidence: 99%
“…The next wave of work relaxed the all-to-all assumption by allowing oscillators to be connected to their nearest neighbors on a one-dimensional chain or ring, a two-dimensional square grid, or a higherdimensional cubic lattice [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . More recently, many researchers have explored the Kuramoto model on more complex topologies, allowing for nonlocal coupling 22 and small-world, scale-free, or other network architectures 6,7 .…”
Section: Introduction a The Kuramoto Modelmentioning
confidence: 99%
“…These correspond to the segments of 25 oscillators within which the integration was exact in Ref. [9]. The two phase transitions separate three phases.…”
mentioning
confidence: 98%
“…For a long time, model studies only revealed negative or inconclusive results regarding the existence of such a phase transition [8]. Recently, we proved that it was present in a one-dimensional chain of pulse-coupled oscillators [9]. A finite critical coupling strength g c was found, at which global frequency entrainment settles.…”
mentioning
confidence: 98%
See 2 more Smart Citations